2013
DOI: 10.1182/blood-2012-02-413831
|View full text |Cite
|
Sign up to set email alerts
|

TLR4- and TRIF-dependent stimulation of B lymphocytes by peptide liposomes enables T cell–independent isotype switch in mice

Abstract: Immunoglobulin class switching from IgM to IgG in response to peptides is generally T cell-dependent and vaccination in T cell-deficient individuals is inefficient. We show that a vaccine consisting of a dense array of peptides on liposomes induced peptidespecific IgG responses totally independent of T-cell help. Independency was confirmed in mice lacking T cells and in mice deficient for MHC class II, CD40L, and CD28. The IgG titers were high, long-lived, and comparable with titers obtained in wild-type anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…Additionally, in the I/R and HMGB1 groups, the lymphocyte levels were higher in the WT mice than in the TLR4 -/-mice, suggesting that the TLR4 loss-of-function may alleviate lymphocytic infiltration. Pihlgren et al demonstrated that the T cell-independent (TI) IgG response was strictly dependent on the ligation of TLR4 receptors on B cells, and TLR ligand is assembled and appropriately presented directly to B lymphocytes [40]. In addition, TLRs has been shown to mediate the innate immune responses, and HMGB1 produced by monocytes/macrophages binds to TLR4 after I/R [22].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the I/R and HMGB1 groups, the lymphocyte levels were higher in the WT mice than in the TLR4 -/-mice, suggesting that the TLR4 loss-of-function may alleviate lymphocytic infiltration. Pihlgren et al demonstrated that the T cell-independent (TI) IgG response was strictly dependent on the ligation of TLR4 receptors on B cells, and TLR ligand is assembled and appropriately presented directly to B lymphocytes [40]. In addition, TLRs has been shown to mediate the innate immune responses, and HMGB1 produced by monocytes/macrophages binds to TLR4 after I/R [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle vehicles, such as polymer particles or liposomes, can promote adjuvant transport through lymphatics to draining lymph nodes (dLNs), while blocking dissemination into the systemic circulation (25,26). Concentration of molecular adjuvants in lymph nodes (LNs) using nanoparticle carriers can enable profound dose sparing of molecular adjuvants, and this approach has been demonstrated for a number of TLR agonists, including MPLA, CpG DNA, poly(I:C), and small-molecule TLR7/8 compounds (27)(28)(29)(30)(31)(32)(33). Importantly, a number of TLR agonist-carrying particle formulations have been demonstrated to effectively adjuvant the immune response when simply admixed with particulate or soluble antigen, i.e., without requiring coincorporation of antigen and adjuvant together in particles (32,(34)(35)(36).…”
Section: Cd8αmentioning
confidence: 99%
“…Addition of the NF- κ B inhibitor, JSH-23, restrained IgE secretion in Trif −/− B cells but had little effect on IgG1 secretion compared to WT B cells. These results demonstrated that constitutive activation of NF- κ B driven by TRIF signaling pathway is essential for class switching to IgE in mouse B cells [38]. Thus, MyD88 and TRIF pathways play different roles in regulating TLR4-induced immune responses in B cells.…”
Section: Signaling Pathway Of Tlr4 In B Cells In Apsmentioning
confidence: 98%